Levels of Nonlethal Force: An Examination of Individual, Situational, and Contextual Factors - Najaka, Stacy Brooke; Rocha, Carlos M.; Kearley, Brook W. (Journal of research in crime and delinquency, 2007)
This work examines the determinants of the levels of nonlethal force employed by Philadelphia police using 1 year of archival self-reports N = 747. Integrated, ordinal multilevel models attend to officer, situational, and contextual determinants of levels of force. The current work seeks to improve on earlier work in several ways. The use of multilevel models reveals whether levels of force vary across locales. In addition, treating the outcome as an ordinal variable and making weaker measurement assumptions reveal different patterns of predictors than seen in earlier works. Key theoretical ideas tested include Smith's suggestion that mixed racial composition of the locale increases the forcefulness of the response, Black's idea that officer-citizen racial combinations affect forcefulness, and Klinger's concept of police vigor and its variation across contexts. Some support is also found for Toch's suggestion that there may be violence-prone police officers. ABSTRACT FROM AUTHOR